Analisis Yuridis terhadap Tindakan Perluasan Lahan diluar Hak Guna Usaha Oleh Korporasi (Studi Kasus di Kecamatan Tempilang, Kabupaten Bangka Barat) - Revaldo; Roni, Istamar Satrio Wibowo; Antrag, Imanuel La (Consensus : Jurnal Ilmu Hukum, 2025)
This study was motivated by the phenomenon of corporations expanding their land beyond the boundaries of their cultivation rights (HGU), which raises criminal law issues. These actions have an impact on land ownership by communities in several villages in the Tempelang subdistrict, environmental damage, and agrarian order. This study aims to analyze the qualifications of land expansion outside of land use rights by corporations in the Tempelang sub-district, West Bangka, from a criminal law perspective and to examine the legal interpretation of these actions because, so far, these actions have only been viewed as violations of private law and cannot have criminal implications. This study uses a normative legal research method, with a legislative approach and a case approach. Data was obtained through literature studies, legal documents, and secondary legal materials in the form of interviews, which were then analyzed qualitatively. This study is expected to contribute, particularly in clarifying legal events and actions, in this case land expansion beyond land use rights by corporations, as well as strengthening law enforcement regarding land expansion beyond land use rights and providing recommendations for improvements in regulation and implementation in the field.